Gambaran Pengetahuan Masyarakat tentang Pencegahan Penyakit Malaria di Desa Tatelu Kecamatan Dimembe - Randy, Taufik; Ottay, Ronald; Palandeng, Henry M. F. (UNIVERSITAS SAM RATULANGI, 2013)
Background: Malaria is a contagious disease which caused by Plasmodium sp. that attack red blood cells. Indonesiahad five species of the malaria parasites. Method: The study is a descriptive study with survey method. This studytook place in Tatelu Village and was done during November to December 2012 with respondents of 120 families.Sampling is by using the simple random sampling. Result: There was 75% for the respondents who know about malaria.The respondents who did not know that Plasmodiums cause malaria was 70,8% and the respondents who didnot know about the symptomps of malaria was 65,8%. Up to 73,4% respondents did not know anything how to protectthemselves from malaria. Conclusion: The villagers of Tatelu did not have a sufficient knowledge about malariaeradication. This was most likely caused by the lower study level and low socioeconomy level. However, the villagerrealised the dangerous of this disease, so they wanted that malaria will not be a threat for their health.Keywords: Spesies, Malaria, parasite, Plasmodium